Pengembangan Destinasi RiverSide Camp, Upaya menjadi Ruang Edukasi dan Ekologi - Hasrun Afandi Umpu Singa (Scimadly Publishing, 2022)
RiverSide Camp is a tourist place that is part of the Ki Hajar Dewantara park, whose management has not been fully functional, as can be seen from the inadequate facilities and a lot of scattered garbage and the absence of a clear icon for RiverSide Camp tourism. This service aims to develop RiverSide Camp with an approach ecology and education in order to create an eco-friendly tourist place arrangement, adequate facilities and have its own icon for the tourist spot. The result of the service is the creation of tourist attractions whose development is synergistic with ecological and educational values. Suggestions for Riverside management should bring up cooperation with parties in sustainable waste management and can be of economic value, adding tourist facilities with ecological concepts, synergizing educational activities at events that will be carried out by Riverside Camp.